A experiência de modernização da administração pública do estado da Bahia nos últimos cinquenta anos (1995 a 2004) - Vieira, Marcelo Rodrigues (2006)
In the last decades there has been a strong trend for the modernization of the apparatus of the Brazilian State in which the planning of the actions starts to hold a special position in public management. At the same time, in a causal relation, it is possible to observe a process of consolidation of the democratic institutions which allows the social agents to evaluate the role performed by the government based on socioeconomic indicators, which include the MHDI (Municipal Human Development Index), the state GDP and the GDP per capita. This work reports a research done on Bahia s public administration modernization process in the last 50 years (1955 to 2004) aiming to evaluate the government actions and the socio-economic indicators performance, comparing them to other states and the same indicators in different regions of the state. Concerning modernization, the reference adopted in the research considers the first Bahia s economic plan the one dated 1956 and the 1966 administrative reform, such as its political, economic and social implications on the subsequent periods as, for instance, the political-institutional adequacy, the institutional division of work, the appearance of the carlismo and the destatization program that adopts, as a strategy, the outsourcing of public services. The modernization is related, also, to the adherence of the state of Bahia to the new process and systems in the administrative system, as well as in the finance and planning systems, basic to guide their political actions. For a better understanding of the effects produced by this modernization process, and comparing them at national and state levels, Bahia s spatial policy was emphasized through the theories of localization and the urban zones, with the contribution of geographers. The regionalization process in substitution to the physiographical zones is considered an important step for planning in a modern concept. The governmental efforts, from the budget and the institutional point of view, are translated into public expenditure by government function, and in the search for regionalization. This ended up in a conceptual change from an Entrepreneur State to a simply planning and regulating state in terms of economic and social activities. Considering this whole process, it is disappointing to verify that this state, considered one of the six with better economic performances in the country as measured by the GDP, is not able to transfer to its population the results of its richness.